Analysis of the Need for English as the Medium of Instruction: A Case Study at MTS Istiqlal - Paksi, Galuh Raga; Cahyadi, Wahyo (English Department, University of Riau Kepulauan, Batam,Indonesia, 2024)
This study investigates the need for English as the medium of instruction (EMI) at MTS Istiqlal, focusing on teachers' English language proficiency, their challenges, and the perceptions surrounding the use of English in the classroom. A qualitative needs analysis was conducted with 20 teachers from MTS Istiqlal, using a survey and semi-structured interviews to assess their language proficiency, confidence in using English, and their perceived needs for improvement. The survey results revealed significant gaps in teachers' confidence, particularly in speaking and explaining subject content in English. A majority of teachers expressed a strong desire for professional development, particularly in speaking, listening, and pedagogical strategies for integrating English into their teaching. The findings suggest the importance of a structured language training program, incorporating both formal instruction and informal practice opportunities, to support teachers in becoming more confident and effective in using English as the medium of instruction. The study highlights the need for tailored professional development programs that address the diverse educational backgrounds and teaching experiences of the teacher, with the ultimate aim of improving teaching quality and supporting the use of English in the classroom.